A purine-rich element in foamy virus pol regulates env splicing and gag/pol expression. Issue 1 (December 2017) - Moschall, Rebecca; Denk, Sarah; Erkelenz, Steffen; Schenk, Christian; Schaal, Heiner; Bodem, Jochen
Abstract Background The foamy viral genome encodes four central purine-rich elements localized in the integrase-coding region ofpol . Previously, we have shown that the first two of these RNA elements (A and B) are required for protease dimerization and activation. The D element functions as internal polypurine tract during reverse transcription. Peters et al., described the third element (C) as essential forgag expression suggesting that it might serve as an RNA export element for the unspliced genomic transcript. Results Here, we analysedenv splicing and demonstrate that the described C element composed of three GAA repeats known to bind SR proteins regulatesenv splicing, thus balancing the amount ofgag /pol mRNAs. Deletion of the C element effectively promotes a splice site switch from a newly identifiedenv splice acceptor to the intrinsically strong downstream localisedenv 3′ splice acceptor permitting complete splicing of almost all LTR derived transcripts. We provide evidence that repression of thisenv splice acceptor is a prerequisite forgag expression. This repression is achieved by the C element, resulting in impaired branch point recognition and SF1/mBBP binding. Separating the branch point from the overlapping purine-rich C element, by insertion of only 20 nucleotides, liberated repression and fully restored splicing to the intrinsically strongenv 3′ splice site. This indicated that thecis -acting element might repress splicing by blocking the recognition of essential splice site signals. Conclusions The foamy viral purine-rich C element regulates splicing by suppressing the branch point recognition of the strongestenv splice acceptor. It is essential for the formation of unsplicedgag and singly splicedpol transcripts.